2017
DOI: 10.1097/mib.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors of Clostridium difficile Infection in Hospitalized Patients With Pouchitis

Abstract: It seems that CDI was limited to pouchitis with underlying IBD and rare in those with underlying FAP. Patients with nonalcoholic fatty liver disease, obesity, and obstructive sleep apnea are at an increased risk of C. difficile pouchitis among patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
5
2
1
Order By: Relevance
“…In comparison to previous smaller studies, we did not observe male gender, preoperative left-sided colitis, lower BMI, or medical comorbidities to be risk factors for pouch CDI[18, 19]. Common risk factors for CDI in the general population include recent antibiotic use, gastric acid suppression therapy use, and hospital admission; however, none of these were observed to be significantly associated with pouch CDI in our population[10-12].…”
Section: Discussioncontrasting
confidence: 92%
“…In comparison to previous smaller studies, we did not observe male gender, preoperative left-sided colitis, lower BMI, or medical comorbidities to be risk factors for pouch CDI[18, 19]. Common risk factors for CDI in the general population include recent antibiotic use, gastric acid suppression therapy use, and hospital admission; however, none of these were observed to be significantly associated with pouch CDI in our population[10-12].…”
Section: Discussioncontrasting
confidence: 92%
“…In addition to patient and clinical factors that have previously been associated with CDI, the authors evaluated the association between body mass index (BMI) and CDI. Prior data from the same group had suggested that obesity and the obesity-related diseases, non-alcoholic fatty liver disease (NAFLD) and obstructive sleep apnea (OSA) were associated with increased risk of CDI among IBD patients with IPAA [6]. In contrast, the current study by Gosai et al found that obesity was independently associated with a lower risk of CDI according to multivariable analysis.…”
contrasting
confidence: 78%
“…Until recently, the description of CDI in IPAA patients has been limited to case reports and case series, which were reviewed in detail by Seril and Shen in 2014 [5]. A recent population-based study using administrative data identified 3470 IBD patients admitted to hospital with pouchitis, estimating that CDI occurs in 2.6% of these admissions [6]. Furthermore, there is a literature showing that CDI of the pouch may be manifest with more systemic symptoms (e.g., fever, night sweats, and weight loss) and is associated with higher rates of recurrent CDI and refractory infection [5].…”
mentioning
confidence: 99%
“…Those with sepsis more often had inflammation in the upper pouch only, and although some had a collection that could be drained radiologically, outcomes were poor with most remaining on long-term antibiotics and nearly a third having a defunctioning stoma or pouch excision 293. In patients with chronic pouchitis 20%–30% have secondary causes for their symptoms, which include CMV infection, Candida , Clostridium difficile, 295 ischaemia, autoimmune disorder, or damage from radiotherapy, chemotherapy or non-steroidal anti-inflammatory drugs 180 296. A proportion may have Crohn’s disease, with reported frequency ranging from 3.6%–13% 297…”
Section: Ulcerative Colitismentioning
confidence: 99%